TabZIP74 Acts as a Positive Regulator in Wheat Stripe Rust Resistance and Involves Root Development by mRNA Splicing - Wang, Fengtao; Lin, Ruiming; Li, Yuanyuan; Wang, Pei; Feng, Jing; Chen, Wanquan; Xu, Shichang (Frontiers in Plant Science, 2019)
Basic leucine zipper (bZIP) membrane-bound transcription factors (MTFs) play important roles in regulating plant growth and development, abiotic stress responses and disease resistance. Most bZIP MTFs are key components of signaling pathways in endoplasmic reticulum (ER) stress responses. In this study, a full-length cDNA sequence encoding bZIP MTF, designated TabZIP74, was isolated from a cDNA library of wheat near-isogenic line of Taichung29*6/Yr10 inoculated with an incompatible race CYR32 of Puccinia striiformis f. sp. tritici (Pst). Phylogenic analysis showed that TabZIP74 is highly homologous to ZmbZIP60 in maize and OsbZIP74 in rice. The mRNA of TabZIP74 was predicted to form a secondary structure with two kissing hairpin loops and could be spliced, causing an open reading frame shift immediately before the hydrophobic region to produce a new TabZIP74 protein without the transmembrane domain. Pst infection and the abiotic PEG and ABA treatments lead the TabZIP74 mRNA splicing in wheat seedling leaves, while both spliced and unspliced forms in roots were detected. In confocal microscopic examination, TabZIP74 is mobilized into the nucleus from the membrane of tobacco epidermal cells in response to wounding. Knocking down of TabZIP74 with barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) enhanced wheat seedling susceptibility to stripe rust and decreased drought tolerance and lateral roots of silenced plants. These findings demonstrated that TabZIP74 mRNA is induced to splice when stressed by biotic and abiotic factors, acts as a critically positive regulator for wheat stripe rust resistance and drought tolerance, and is necessary for lateral root development.